Overview of metal contacts technology on semiconductor - Bhari, Bibi Zulaika; Ali, Ahmad Hadi (Penerbit UTHM, 2020)
Over the past decades, researcher confronts new difficulties and breakthrough due to semiconductor innovation and these chances are evident in the endeavours that have been laid by semiconductor and optoelectronic devices. Semiconductor defined as a material which conducts electricity conditionally, hence making it useful in controlling for optoelectronic devices. It possesses intermediate conductivity, ranging between a conductor and an insulator. The superiority of metal-semiconductor plays a significant role in the performances of semiconductor devices and it is a powerful tool for improving performance in many areas of modern life.